Use of Both Serum Cystatin C and Creatinine as Diagnostic Criteria for Cardiac Surgery-Associated Acute Kidney Injury and Its Correlation with Long-Term Major Adverse Events - Miaolin Che; Xudong Wang; Bo Xie; Ritai Huang; Shang Liu; Yucheng Yan; Mingli Zhu; Renhua Lu; Jiaqi Qian; Weiming Zhang; Leyi Gu; Shan Mou; et al. (Kidney & Blood Pressure Research, 2019)
Background/Aims: Cardiac surgery-associated acute kidney injury (CSA-AKI) was traditionally defined as an increase in serum creatinine (sCr) after cardiac surgery. Recently, serum cystatin C (sCyC) has been proposed to be a better biomarker in the prediction of AKI. The clinical utility and performance of combining sCyC and sCr in patients with AKI, particularly for the prediction of long-term outcomes, remain unknown. Methods: We measured sCyC together with sCr in 628 patients undergoing cardiac surgery. sCyC and sCr were assessed at baseline and 24 and 48 h after surgery. CSA-AKI determined by sCr (CSA-AKIsCr) was defined as an sCr increase greater than 0.3 mg/dL or 50% from baseline. Major adverse events (MAEs; including death of any cause and dialysis) at 3 years were assessed. Results: CSA-AKIsCr developed in 178 patients (28.3%). Three-year follow-up was available for 621 patients; MAEs occurred in 42 patients (6.8%). An increase in sCyC concentration ≥30% within 48 h after surgery was detected in 228 patients (36.3%). This was the best sCyC cutoff for CSA-AKIsCr detection (negative predictive value = 88.8%, positive predictive value = 58.3%). To evaluate the use of both sCyC and sCr as CSA-AKI diagnostic criteria, we stratified patients into 3 groups: non-CSA-AKI, CSA-AKI detected by a single marker, and CSA-AKI detected by both markers. By multivariable logistic regression analysis, the independent predictors of MAEs at 3 years were group 2 (non-CSA-AKI group as the reference, CSA-AKI detected by a single marker: odds ratio [OR] = 3.48, 95% confidence interval [CI]: 1.27–9.58, p = 0.016), group 3 (CSA-AKI detected by both markers: OR = 5.12, 95% CI: 2.01–13.09; p = 0.001), and baseline glomerular filtration rate (OR = 2.24; 95% CI: 1.27–3.95; p = 0.005). Conclusion: Combining sCyC and sCr to diagnose CSA-AKI would be beneficial for risk stratification and prognosis in patients after cardiac surgery.